Key factors for an improved lithium ion storage capacity of anodic TiO2 nanotubes - Kirchgeorg, Robin; Kallert, Max; Liu, Ning; Hahn, Robert; Killian, Manuela; Schmuki, Patrik (Electrochimica Acta, 2016)
In the present work we investigate key factors that influence the Li-storage capacity of anodically grown self-organized TiO2 nanotube layers. First, the influence of both tube length and top morphology are investigated regarding the rate performance of the nanotube layers. Then, factors such as the presence of initiation (grass) layers and the influence of the double walled morphology of conventional TiO2 nanotube layers are elaborated. At high C-rates a grass layer even shows a beneficial contribution, mainly by adding to the double layer capacitance. The presence of a double wall morphology and the associated carbon contamination lead to a lower intercalation ability. Two different approaches are taken to eliminate the inner carbon-rich layer: Cathodic polarization and tube formation in DMSO based electrolytes. This results in an enhancement of the areal capacity by 17% and 33% compared to unmodified tube layers for the two approaches.
EAM Import::2019-03-12